2017
DOI: 10.3839/jabc.2017.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and antioxidant activities ofBouea macrophyllaGriffith in Nakhon Nayok province

Abstract: Genetic differentiation and antioxidant activities in ethanolic extracts from leaves of Bouea macrophylla Griffith were determined. The result revealed genetic differentiation among sour ma-praang, ma-yong and sweet ma-praang of B. macrophylla Griffith (φ PT =0.772, p-value=0.000). In addition, high genetic diversities were found in sour ma-praang and sweet ma-praang populations (P: 51.4 and 57.1 %; He: 0.1900.035 and 0.2240.036, respectively), but low genetic diversity was found in ma-yong population (P: 8.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…This is higher than that of the ripe fruit that were in the range of 0.012–0.020 mg GAE/mg MPFEs. Our results are similar to that of Thummajitsakul and Silprasit who reported that the TPC 95% etanolic leave extracts ranged from high to low levels, with mayong chid being the highest at 0.701 mg GAE/mg MPLEs, maprang prieyo at 0.680 mg GAE/mg MPLEs, and maprang wan at 0.531 mg GAE/mg MPLEs [28]. Andina and Musfirah found that the TPC was 0.137 mg GAE/mg MPCEs and 0.068 mg GAE/mg MPLEs for the ethanolic extraction of Ramania (Maprang) cortex and leaves, respectively [29].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is higher than that of the ripe fruit that were in the range of 0.012–0.020 mg GAE/mg MPFEs. Our results are similar to that of Thummajitsakul and Silprasit who reported that the TPC 95% etanolic leave extracts ranged from high to low levels, with mayong chid being the highest at 0.701 mg GAE/mg MPLEs, maprang prieyo at 0.680 mg GAE/mg MPLEs, and maprang wan at 0.531 mg GAE/mg MPLEs [28]. Andina and Musfirah found that the TPC was 0.137 mg GAE/mg MPCEs and 0.068 mg GAE/mg MPLEs for the ethanolic extraction of Ramania (Maprang) cortex and leaves, respectively [29].…”
Section: Resultssupporting
confidence: 90%
“…Andina and Musfirah found that the ethanolic extraction of the maprang cortex and leaves scavenged DPPH radicals by IC 50 at 20.03 μg/mL and 55.83 μg/mL, respectively [29]. Thummajitsakul and Silprasit reported that the ethanolic extracts obtained from the leaves of three maprang varities, maprang prieyo, mayong chid, and maprang wan, exhibited 50% ABTS ·+ scavenging activity with (EC 50 ) being 0.24 ± 0.08, 0.73 ± 0.07, and 0.70 ± 0.06, respectively [28]. In terms of the influence of the extraction solvents on antioxidant activity, Onivogui et al.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids possess scavenging or chelating antioxidant activity [24,25]. A previous study also revealed that the leaves of B. macrophylla had potent antioxidant activity using the ABTS free-radical scavenging and metal chelating assays [7]. In this study, the results of two assays-FRAP (total electron transfer-based) and DPPH (hydrogen atom transfer-based)-revealed that the plant extract exhibited strong antioxidant activity.…”
Section: Plant Metabolite Profile Of B Macrophylla Ethanol Extractmentioning
confidence: 51%
“…The antibacterial activity determined for various concentrations of the B. macrophylla extract has not been reported previously [5,7,21]. This study investigates for the first time the antimicrobial properties of a B. macrophylla extract in vitro.…”
Section: Antibacterial Activitymentioning
confidence: 86%
“…Since it is more abundant, less expensive, and easier to harvest without seasonal limitation. Various active compounds in mapraang/gandaria have been confirmed by Thummajitsakul and Silprasit (2017). In Indonesia, Andina and Musfirah (2017) have found several active compounds of ramania/gandaria leaf cortex extract from South Kalimantan.…”
Section: Introductionmentioning
confidence: 91%